2013
DOI: 10.1093/cercor/bht208
|View full text |Cite
|
Sign up to set email alerts
|

Time- but Not Sleep-Dependent Consolidation of tDCS-Enhanced Visuomotor Skills

Abstract: Consolidation of motor skills after training can occur in a time- or sleep-dependent fashion. Recent studies revealed time-dependent consolidation as a common feature of visuomotor tasks. We have previously shown that anodal transcranial direct current stimulation (tDCS) in combination with repeated motor training benefits consolidation by the induction of offline skill gains in a complex visuomotor task, preventing the regular occurrence of skill loss between days. Here, we asked 2 questions: What is the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
146
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(172 citation statements)
references
References 53 publications
(90 reference statements)
14
146
2
1
Order By: Relevance
“…This may be particularly important for a technique like tDCS (which may exert its effect through the alteration of thresholds for neuronal discharge (Fritsch et al, 2010)) as observed effects may be highly dependent on the specific context in which it is applied. Currently, the most frequently used tasks to investigate motor skill learning in experimental settings are: (1) sequential finger tapping tasks (SFTT; which can include either implicit or explicit sequence structure) (Ghilardi, Moisello, Silvestri, Ghez, & Krakauer, 2009;Nitsche et al, 2010;Reis et al, 2015;Song & Cohen, 2014); and (2) the sequential visual isometric pinch force task (SVIPT) (Reis et al, 2009). In a sense, these tasks are complimentary in that for the SFTT, the main unit of action is rather trivial for a healthy subject to accomplish (i.e.…”
Section: Motor Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be particularly important for a technique like tDCS (which may exert its effect through the alteration of thresholds for neuronal discharge (Fritsch et al, 2010)) as observed effects may be highly dependent on the specific context in which it is applied. Currently, the most frequently used tasks to investigate motor skill learning in experimental settings are: (1) sequential finger tapping tasks (SFTT; which can include either implicit or explicit sequence structure) (Ghilardi, Moisello, Silvestri, Ghez, & Krakauer, 2009;Nitsche et al, 2010;Reis et al, 2015;Song & Cohen, 2014); and (2) the sequential visual isometric pinch force task (SVIPT) (Reis et al, 2009). In a sense, these tasks are complimentary in that for the SFTT, the main unit of action is rather trivial for a healthy subject to accomplish (i.e.…”
Section: Motor Learningmentioning
confidence: 99%
“…The effects of anodal tDCS on online sequence learning have been a particular area of interest (Amadi, Allman, Johansen-Berg, & Stagg, 2015;Ambrus et al, 2016;Cuypers et al, 2013;Kang & Paik, 2011;Kantak, Mummidisetty, & Stinear, 2012;Karok & Witney, 2013; M. F. Kuo et al, 2008;Nitsche et al, 2010;Nitsche et al, 2003;Reis et al, 2015;Reis et al, 2009;Stagg, Jayaram, et al, 2011;Tecchio et al, 2010;Vines, Cerruti, & Schlaug, 2008;Wade & Hammond, 2015). In an initial study, Nitsche and colleagues (2003) showed that anodal tDCS applied over M1 concurrently with training improved online implicit learning of a motor sequence, while stimulation applied to PMd, DMPFC and DLPFC did not .…”
Section: Online Motor Performance and Skill Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we anticipated increased activation beneath the anode during WM and EF in the real tDCS group; in the former task activation change would correlate with task performance after consolidation [37,38]. At the system level we expected reduced activation in the task relevant WM and EF networks in the real tDCS group [30]; the bilateral parietal cortex and ACC respectively [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 92%